Antioxidant and anti-inflammatory activities of Phlomis pungens and Coridothymus capitatus - YAVUZ, AYŞE NUR; EMRE, GİZEM; BİTİŞ, LEYLA; KABASAKAL, LEVENT; ÇAM, MUHAMMET EMİN (MARMARA UNIV, FAC PHARMACY, 2018)
The purpose of this study was to comparatively reveal for the first time the antioxidant, anti-inflammatory effects of Phlomis pungens and Coridothymus capitatus methanol extracts obtained by using maceration extraction method. According to the results of anti-inflammatory activity, P. pungens methanolic extract demonstrated a more prominent and intensive antiinflammatory effect with 24.7% of inhibitive capacity in the altered edema size after the first hour of carrageenan injection compared to C. capitatus methanolic extract. P. pungens methanolic extract inhibitory effect increased during three hours and reached maximum by 41.9%. According to the results obtained from antioxidant activity experiments, methanol extract of C. capitatus exhibited stronger free radical scavenging (DPPH), cupric reducing (CUPRAC), ferric reducing/antioxidant power (FRAP) and ABTS radical cation scavenging activity than P. pungens extract. In additon, C. capitatus extract had higher ABTS radical cation scavenging and ferric reducing/antioxidant power activity than ascorbic acid, BHT and BHA, respectively. Therefore, this extract can be used in both medicine and food industry as a natural antioxidant source.
Keywords: C. capitatus; P. pungens; antioxidant; anti-inflammatory; IN-VITRO ANTIOXIDANT; ESSENTIAL OILS; CHEMICAL-COMPOSITION; PLANTS; EXTRACT; WILD